Dualism of Subsidiaries in Indonesia: Between Juridical Independence and Economic Dependence of Subsidiaries in a Group of Companies - Annurdi Nurdi; Budi Santoso; Hanif Nur Widhiyanti; Reka Dewantara (Societas et Iurisprudentia, 2024)
In the limited liability company law currently in force in Indonesia, holding company and subsidiaries in the form of limited liability companies are seen as independent and separate legal entities, where each company has the right to independently carry out legal actions in accordance with the company’s interests. This differs from the concept of “group of companies” which consists of a collection of legally independent companies, where the subsidiaries are controlled by the holding company. This kind of concept raises fundamental questions considering that there is a contradiction between the principle of independence possessed by the company as an independent legal entity on one hand, and the reality of control by the holding company over its subsidiaries as a unitary economic entity. To answer this kind of problem, our paper offers a systematic explanation based on a normative and case approach to the company’s legal regime in Indonesia. This paper argues that the contradiction between the principle of independence and the reality of control by a parent company over its subsidiaries as an economic unit has the potential to prevent subsidiaries from moving independently based on their own business interests. The amount of control authority that the holding company has over its subsidiaries – as this paper will show – must be exercised by taking into account several things, including: the control does not conflict with legal regulations, does not cause losses to the subsidiaries, and does not harm the interests of the third parties as the limitation of control by the holding company.